Preconditions for the Successful Segmental Step-Wise Reconstruction of the Global Function of the Upper Extremity in Case of the Complete Brachial Plexus Injury (Case Report) - Hatskyi, O.O.; Tretiak, I.B.; Tsymbaliuk, V.I.; Chyrka, Yu.L.; Jiang, Hao; Tsymbaliuk, Ya.V.; Tretiakova, A.I. (TERRA ORTHOPAEDICA, 2023)
Background. The prognosis of recovery of the distal muscles (dM) of the upper extremity (UE) in complete brachial plexus injuries (cBPI) after any selective nerve transfer (NT) is poor. Free functioning muscle transfer (FFMT) is deprived of the disadvantages of NT. By combining NT and FFMT one can achieve recovery of the global functionality of UE in cBPI. Objective: to define theoretical and clinical preconditions for each stage (S) of the segmental reconstruction of UE in cBPI. Materials and Methods. 38 years old male patient 3 months after cBPI underwent NT (S1) of the phrenic to musculocutaneous nerve; branches of the spinal accessory nerve were transferred to axillary and suprascapular nerves. 36 months after S1 the patient underwent wrist (WA) and trapeziometacarpal arthrodesis (TMCA) (S2). 43 months after S1 the patient underwent FFMT of the gracilis muscle (S3). Clinical and neurological, electroneuromyographic (EMG), and X-ray examinations were carried out within the expected time to achieve the expected result after the corresponding stages of reconstruction. Results. 26 months after S1 m. biceps brachii and m. deltoideus recovered to M4; m. supra-infraspinatus ineffectively recovered to M3. A stable arthrodesis effect in WA and TMCA was achieved after 42 months in general. Poor clinical and EMG recovery of the gracilis muscle (S3) within the expected time led to indefinite postponement of S4, with clinical and EMG control every 3 months. Conclusions. Clinical signs of functional recovery cannot be a prerequisite for using a primary recipient nerve as a secondary donor nerve; the number of motor fibers in the donor nerve must be confirmed by objective data of morphometric and histochemical express methods; theoretical preconditions of the “sitting donor” technique appear to be the most promising in terms of recovery of dM of UE.